DE LANGE, J Inventory of documents - DE LANGE, J (ARCA, 2018)
Repatriation loan (1 November 1902) and death certificate of H.W.W. Heinze (16 April 1915)
COVERAGE 1902-1915; 0.02 metre
Keywords: DE LANGE, J; Inventories